المعوقات التي تحد من التحول نحو الإدارة الإلكترونية في هيئة الرقابة الإدارية دراسة حالة بهيئة الرقابة الإدارية فرع إجدابيا - القطراني خالد إقليوان (Scientific Journal of University of Benghazi, 2020)
Abstract: The aim of the study is to identify the most important obstacles (human, administrative, financial, and technical) that limit the shift towards electronic management, as the problem of the study crystallized in the question: What are the obstacles that limit the transformation towards electronic management in the Administrative Control Authority? Employees out? While the importance of the study was that it clarified the obstacles that limit the shift towards electronic management, and the researcher used the descriptive approach (arithmetic averages, standard deviations, and the relative importance of all obstacles), where the researcher relied on questionnaires as a tool for study and statistical analysis spss to analyze the data, descriptively and inferred. Questionnaires on the investigators, where the research community was represented by all workers in the Administrative Control Authority, Ajdabiya Branch, who numbered (20). The study concluded, and the study concluded with the most important results, which are the weakness of government support (legislation) for the application of electronic management, the shortage of specialists in information and communication technology The most prominent recommendations were the necessity of reducing administrative obstacles by supporting senior management, the policy of implementing electronic management.